2020
DOI: 10.1002/ceat.201900638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti‐Encrustation Additives on Zirconium Molybdate Hydrate

Abstract: Anti-encrustation additives were mainly investigated in nitric acid solution with zirconium (Zr), molybdenum (Mo), and tellurium (Te) to prevent the encrustation of zirconium molybdate hydrate (ZMH). The ZMH generated by reaction crystallization of Mo and Zr as main fission products has a high adhesion property in spent nuclear fuel reprocessing. In addition, it is reported that Te, which is also one of the fission products, precipitates together with ZMH. Encrustation of precipitates containing Te was effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Lower supersaturation also affects the crystallization process adversely as the driving force for both the crystallization and encrustation is the same . Chemical additives have also been used to suppress the encrustation . The other usage of additives includes control of morphology or polymorphs during crystallization. , However, in some studies, additives are found to suppress nucleation and crystal growth leading to a low yield of crystallization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower supersaturation also affects the crystallization process adversely as the driving force for both the crystallization and encrustation is the same . Chemical additives have also been used to suppress the encrustation . The other usage of additives includes control of morphology or polymorphs during crystallization. , However, in some studies, additives are found to suppress nucleation and crystal growth leading to a low yield of crystallization .…”
Section: Introductionmentioning
confidence: 99%
“…3 Chemical additives have also been used to suppress the encrustation. 14 The other usage of additives includes control of morphology or polymorphs during crystallization. 15,16 However, in some studies, additives are found to suppress nucleation and crystal growth leading to a low yield of crystallization.…”
Section: ■ Introductionmentioning
confidence: 99%